Presidential Policies on Terrorism From Ronald Reagan to Barack Obama - Starr-Deelen, Donna G.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
The book analyzes how the administrations of Ronald Reagan, George H.W. Bush, Bill Clinton, and George W. Bush used force in response to incidents of international terrorism - providing comparison between each of the administrations as they grappled with the evolving nature and role of terrorism in the United States and abroad.
Keywords: Science; Science; Science, general